A Novel Approach Towards Outcome Based Engineering Education for Continuous Quality Improvement: A Case Study - Jakhale, A. R.; Attar, A. C. (Journal of Engineering Education Transformations, 2015)
The Changes in the curriculum of engineering education have been an on-going need to be addressed and practiced by the universities to consistently generate well groomed learners suitable for industry. The Outcome Based Education (OBE) is an education system that emphasis on outcomes measurement rather than inputs of curriculum covered. Outcomes may include a range of knowledge, skills and attitudes. The objective of this study is to present a novel approach for the outcome based assessment of engineering education for Information Technology (IT) department. A case study of an RIT engineering educational organization has been discussed to present novel approach. IT department of the case organization was exposed to the OBE and evaluated for Program-Outcomes (PO) entirely for all courses. In the studied organization the course evaluation was based on In Semester Evaluation (ISE), Mid Semester Evaluation (MSE), End Semester Evaluation (ESE). Mapping of Course Learning Outcome (CLO)-PO was done for the assessment. The feedback from alumnae, employers and students was taken to review course structure and CLO-PO with the highest academic achievements and better understanding of the course based on the OBE. This study shows that, in the studied organization there is positive impact of OBE on engineering education.